ANALISIS SISTEM INFORMASI MANAJEMEN RUMAH SAKIT UMUM TEUNGKU PEUKAN DI ACEH DITINJAU DARI PERENCANAAN - Agustina, Rini Fitri; Zaman, Nasrul; Nurjannah, Nurjannah; Saputra, Irwan; Usman, Said (Poltekkes Kemenkes Bandung, 2024)
The Hospital Management Information System (SIMRS) is an integrated system that regulates the collection of various data, then the data is processed into information needed by stakeholders in the hospital. SIMRS is prepared to handle the entire hospital management process, for this reason a planning process for information system components (KSI) is needed so that it is effective and produces accurate, relevant and consistent data in a timely manner. This research aims to determine the optimization of SIMRS and analyze information system planning (KSI) including infrastructure planning, hardware and software, brainware and technology at Teungku Peukan General Hospital (RSUTP). This research is qualitative research. Data analysis uses a thematic approach. The research subjects were ten top, middle and lower level managers as well as information technology staff who managed SIMRS at RSUTP. The research results show that KSI planning at RSUTP includes making a master plan for the hospital building without a site plan for the internet and electricity network for SIMRS; planning for procurement of computers not with UPS; SIMRS software planning tailored to user needs; there are no working terms of reference for training; not all management teams are involved in technology planning. It can be concluded that the planning of information system components at Teungku Peukan General Hospital has not been optimal and comprehensive.